Multiobjective Prioritization of Preselected Fuel Treatment Strategies for Public Forestland: A Case Study in Flathead County, Montana. Issue 1 (31st August 2017) - Prato, Tony; Paveglio, Travis
Abstract: Preferred fuel treatment strategies (FTSs) were determined for two public forests in Flathead County, Montana, for the period 2010–59 using a multiple-objective evaluation method that accounts for future residential development in the WUI and climate change. Three fuel management objectives were used to evaluate and rank FTSs: minimizing monetary residential losses due to wildfire, minimizing deviation from historical forest ecological conditions, and maximizing net revenue from timber harvesting associated with fuel treatment. Preferred FTSs varied across planning periods for both forests. For the Flathead National Forest, managed by the US Forest Service, there was a unique preferred FTS for each subperiod. For the forest managed by the Montana Department of Natural Resources and Conservation, two spatially prioritized FTSs were equally preferred in period 1, one spatially prioritized FTS was preferred in subperiod 2, no spatially prioritized FTS was preferred in periods 3 and 4, and the three FTSs were equally preferred in period 5. Results suggest that evaluating FTSs for a forest on the basis of a single management objective could give misleading results about the most preferred FTS and that targeting fuel treatments based on spatial priorities may not be superior to random allocation of fuel treatments to eligible stands.